Cochlear implants for pre-lingually profoundly deaf adults. (1st April 2016) - Craddock, Louise; Cooper, Huw; Riley, Alison; Wright, Tracy
Abstract : Introduction : Increasing numbers of pre-lingually profoundly deaf adults are seeking a cochlear implant (CI). Pre- and post-operative outcomes are presented on 20 of these patients. Results : An Adult Pre-Lingually Profoundly Deaf Implant Profile (APDIP) weighted the pre-operative level of concern about potential CI benefit. Results indicated no group mean post-operative open-set improvement. However CUNY sentence testing (auditory plus lip-reading cues) revealed improved performance with a CI. Twelve out of 20 patients used their CIs for more than 10 hours per day, suggesting good usage. Moreover, hours of usage were positively associated with measured benefit on CUNY sentences in the lip-reading plus sound via CI condition. There was no apparent relationship between pre-operative level of concern and post-operative CI performance or hours of processor use. Conclusion : Results suggest implantation is beneficial and effective in this group.